Pengaruh Manajemen Piutang Terhadap Profitabilitas Studi Industri Di Tangerang - Mukhlisiah, Rizka; Haryanto, Haryanto (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2025)
Working capital in management is very important for the survival of an organization. It is also important for the growth of an organization. Management of receivables is an important component of working capital management carried out in a company. The current study empirically tests the effect of the efficiency of receivables management as measured by the debtor turnover ratio in the commercial industry in Indonesia on the profitability of the company. Profitability is measured using the returned capital. The study was conducted in the period 2019 to 2021. The findings show a significant positive relationship between the debtor turnover ratio and the company's profitability. This indicates that receivables management must be the main focus in increasing the profitability of industrial companies.